Wooden breast lesions in broiler chickens in the UK - de Brot, Simone; Perez, S.; Shivaprasad, H.L.; Baiker, Kerstin; Polledo, L.; Clark, M.; Grau-Roma, Llorenc (BMJ Publishing Group, 2016)
A new condition causing significant economic losses due to lesions in the pectoralis major muscle of commercial broiler chickens has been recently reported in Finland. The condition has been named wooden breast and is characterized by its gross and histological appearance. Between October 2014 and April 2015, samples from 5 pectoralis major muscles downgraded in the slaughterhouse were submitted to the Veterinary Pathology Service of the University of Nottingham for histological examination. All the five studied samples showed moderate or severe multifocal polyphasic muscular degeneration and necrosis. All cases showed variable degree of interstitial fibrosis and/or presence of adipose tissue within interstitium, as well as formation of small nodular follicle-like aggregates of lymphocytes adjacent to small blood vessels. These lesions are compatible to wooden breast and overlap with another recently reported condition known as white striping. The present communication provides evidence that wooden breast lesions are present in broiler chickens in the UK and discusses its similarities with white striping. Larger studies assessing the prevalence of wooden breast are needed to determine the relative economic importance of this condition in this country.